2017
DOI: 10.2527/jas.2016.1003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in an F2 Duroc x Pietrain resource population for economically important meat quality and carcass traits1

Abstract: Meat quality is essential for consumer acceptance, it ultimately impacts pork production profitability and it is subject to genetic control. The objective of this study was to map genomic regions associated with economically important meat quality and carcass traits. We performed a genome-wide association (GWA) analysis to map regions associated with 38 meat quality and carcass traits recorded for 948 F2 pigs from the Michigan State University Duroc × Pietrain resource population. The F0, F1, and 336 F2 pigs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…It has been widely used in humans (Hindorff et al, 2009 ; Lauc et al, 2010 ; Hoffmann et al, 2017 ) and domestic animals (Petersen et al, 2013 ; Kominakis et al, 2017 ). In pigs, many GWAS have been performed on various economically important traits, including immune traits (Luo et al, 2012 ; Ponsuksili et al, 2016 ), meat quality traits (Casiró et al, 2017 ; Verardo et al, 2017 ), and structural soundness traits (Fan et al, 2011 ). However, few GWAS have been conducted to assess the genetic architecture of PU and FI.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in humans (Hindorff et al, 2009 ; Lauc et al, 2010 ; Hoffmann et al, 2017 ) and domestic animals (Petersen et al, 2013 ; Kominakis et al, 2017 ). In pigs, many GWAS have been performed on various economically important traits, including immune traits (Luo et al, 2012 ; Ponsuksili et al, 2016 ), meat quality traits (Casiró et al, 2017 ; Verardo et al, 2017 ), and structural soundness traits (Fan et al, 2011 ). However, few GWAS have been conducted to assess the genetic architecture of PU and FI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GWAS can be done exploiting results of GBLUP ( Wang et al 2012 ; Dikmen et al 2013 ; Casiró et al 2017 ). Most of these works ( e.g.…”
mentioning
confidence: 99%
“…Our functional analysis showed that RHOD was involved on actin filament organization GO BP (GO: 0061572) ( Table 2 ). RHOD gene maps on the porcine chromosome 2 (5.39 Mb) within a quantitative trait loci (QTL) for shear force detected in the F2 of a Duroc x Pietrain crossbred [ 39 ]. In vitro studies have revealed that the interference of RHOD protein produces a higher cell attachment and diminishes cell migration [ 40 ].…”
Section: Discussionmentioning
confidence: 99%